1993
DOI: 10.1128/iai.61.10.4167-4172.1993
|View full text |Cite
|
Sign up to set email alerts
|

Induction of release of tumor necrosis factor from human monocytes by staphylococci and staphylococcal peptidoglycans

Abstract: The role of cytokines in gram-positive infections is still relatively poorly defined. The purpose of this study was to establish whether or not intact staphylococci and purified peptidoglycans and peptidoglycan components derived from staphylococci are capable of stimulating the release of tumor necrosis factor (TNF) by human monocytes. We show here that intact staphylococci and purified peptidoglycans, isolated from three Staphylococcus epidermidis and three S. aureus strains, were indeed able to induce secre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
76
1
4

Year Published

1993
1993
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 176 publications
(86 citation statements)
references
References 38 publications
5
76
1
4
Order By: Relevance
“…2 Difference in SLPI concentration between pneumonia and pyelonephritis (P 0.004) or infection of central airways (P 0.006). 3 Concentrations below detection limit of assay. 4 Difference in TNF-a concentration between pyelonephritis and central airways (P 0.01) or lower respiratory tract infection (P 0.03).…”
Section: Plasma Slpi Concentration and Size Of Pulmonary Consolidationmentioning
confidence: 99%
“…2 Difference in SLPI concentration between pneumonia and pyelonephritis (P 0.004) or infection of central airways (P 0.006). 3 Concentrations below detection limit of assay. 4 Difference in TNF-a concentration between pyelonephritis and central airways (P 0.01) or lower respiratory tract infection (P 0.03).…”
Section: Plasma Slpi Concentration and Size Of Pulmonary Consolidationmentioning
confidence: 99%
“…Teichoic acid (TA), another important cell wall constituent of Gram-positives, consisting of ribitol phosphate polymers, activates complement via the classical pathway [10]. Whole bacteria of S. epidermidis induce PBM to release TNF, IL-1 and IL-6 [6], while PG has been shown to stimulate PBM to TNF release [11]. PG precursors, which are secreted from penicillin-treated Streptococcus faecalis, are also able to trigger PBM to IL-1 production [12].…”
Section: Introductionmentioning
confidence: 99%
“…We used only HAECs to determine the inflammation-inducible effects of S. oralis RPS, and it is uncertain whether the effects are HAEC specific or not. Polysaccharidecontaining bacterial components such as lipopolysaccharide (Tsoyi et al, 2009;Zhang et al, 2011) and peptidoglycan (Timmerman et al, 1993) have been shown to induce inflammatory responses in human cells. These bacterial components are hetero-type complexes of sugars and lipids/proteins.…”
Section: Discussionmentioning
confidence: 99%